Experimental Investigation on Pervious Recycled Aggregate Concrete Made of Waste Porcelain - Khoshnaw, Ganjeena J.; Younis, Khaleel H.; Hamad, Waleed A.; Ismail, Ayser J.; Jukil, Glpa Ali Mahmood; Jirjees, Firas F.; Yaba, Hozan K.; Maruf, Shelan M. (Salehan Institute of Higher Education, 2024)
The current study examines the physical, mechanical, and durability of eco-efficient pervious concrete produced with partial and complete substitutions of natural aggregate (NA) by recycled aggregate (RA) waste from demolished concrete and porcelain. The experimental investigation assessed the workability (slump test), compressive strength, flexural strength, and tensile strength along with the concrete's water permeability, impact, and abrasion resistance. Seven mixes were examined; the first is a control mix with natural aggregate, and the other six are made with various RA ratios, including 30%, 70%, and 100%. The sand was also fully replaced by waste porcelain, even though the ratio of sand used in pervious concrete was low. The results revealed that using waste concrete and porcelain adversely affected the workability of fresh pervious concrete mixes, reducing it by approximately 14%. Furthermore, a decrease in the strength of pervious concrete was noticed, especially in the splitting tensile strength, where the reduction reached 32%. Moreover, the impact resistance of pervious concrete made with RA reduced by 29% compared to that made with NA; the same applies to durability, with an increase of 20% in weight loss. On the other hand, using both recycled concrete and recycled porcelain improved the permeability of the pervious concrete, which reached 30%. Pervious concrete made with waste concrete and porcelain can be an acceptable alternative to that made from natural aggregate due to its improved water permeability and positive environmental impact. However, further investigation is important to consider strength and durability enhancement. Doi: 10.28991/CEJ-2024-010-09-08 Full Text: PDF